Numerical simulation and thermal enhancement of multi-based nanofluid over an embrittled cone - Azad Hussain (Elsevier, 2021)
The thermal energy enhancement in industries is an important problem today. The daily life application of nanofluid technology has changed the view by increasing heat transfer coefficient, reduction in skin friction, and decreasing production cost. This article focuses on the conventional flow of multi-based nanofluids over the vertical rotating cone, along with heat transfer attributes. Synthetic Ester (SE) and Natural Ester (NE) are used as the base fluids, phenomena of allotrope have been utilized for base fluid to create different combinations of nanofluids such as Ag-NE, Ag-SE, Cu-O-NE, and Cu-O-SE. The flow is induced by cone angular velocity that is dependent on time. The similarity assembly is employed to transform the highly non-linear partial differential equations into non-dimensional partial differential equations. The solution is obtained utilizing the BVP-4c technique in MATLAB, the tolerance for the numerical solution is kept 10−06. The graphical outcomes of velocity profiles and temperature are presented, heat transfer coefficients for different nanofluids have been observed and compared also presented in the tabulated data set. This study recommends more frequent exploitation of Ag-NE and Ag-SE nanofluids, these nanofluids have higher heat transfers as compared to others explored in the examination.